Nonalcoholic steatohepatitis and obesity as one of the main predictors of metabolic syndrome development in children and adolescents - O.Yu. Belousova (Zaslavsky O.Yu., 2017)
This article deals with the importance of isolating the metabolic syndrome in pediatric gastroenterological practice, since almost all the major components of the metabolic syndrome are already found in childhood. In addition, this condition diagnosed at early stages of the disease development is theoretically reversible, that is with the prescription of an adequate treatment, it is possible to reduce the severity of its main manifestations and to prevent diabetes mellitus type 2, dyslipidemia and cardiovascular diseases. The main predictors of the development of this pathology are obesity, whose growth tends to increase constantly, and non-alcoholic steatohepatitis, often manifested in adolescence. The advisability of using drugs that affect hepatic metabolism and are able to exert a lipid-regulating effects, in particular, essential phospholipids, is discussed.